2020
DOI: 10.12669/pjms.36.7.3125
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outbreak, disruption of dental education, and the role of teledentistry

Abstract: The novel coronavirus disease 2019 (COVID-19) has affected the whole world and has now been declared a Pandemic by the World Health Organization (WHO). Although the mortality rate of this virus is low, it is especially potent against people with underlying systemic conditions. Dentistry is a profession where the doctor, as well as the dental staff, works in close vicinity to the patient’s mouth. Dental education has two core components; didactic and clinical training (including patient care). Dental education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 33 publications
0
32
0
10
Order By: Relevance
“…Various routes of transmission of COVID-19 infection have been identified, including human-to-human contact, aerosol, and through an endogenous route. 23 In our study, medical students had a better understanding regarding the mode of transmission, as compared with the dental students. These results are consistent with a study lead by Khan et al, who found that healthcare workers have better knowledge.…”
Section: Discussionmentioning
confidence: 79%
“…Various routes of transmission of COVID-19 infection have been identified, including human-to-human contact, aerosol, and through an endogenous route. 23 In our study, medical students had a better understanding regarding the mode of transmission, as compared with the dental students. These results are consistent with a study lead by Khan et al, who found that healthcare workers have better knowledge.…”
Section: Discussionmentioning
confidence: 79%
“…One way to help improve and develop students’ intuitive minds in this modernized technological environment is by utilizing electronic resources to actively indulge students to facilitate effective teaching and learning processes through E-learning. 42 …”
Section: Resultsmentioning
confidence: 99%
“… References should not be used in the conclusion unless the journal allows it. The reason for referencing the article by Farooq et al (2020 1 ) is that it contains relevant information regarding e-learning during covid-19 and it is very current (2020) and the authors should use it as a reference in their discussion instead of articles that are a decade old. …”
mentioning
confidence: 99%
“…In the web-based virtual environment, students can continue to engage with live academic lectures that were previously available in classrooms [ 16 ] and can also store and review these lectures whenever and wherever they choose. On the other hand, the use of virtual patients helps dental students develop clinical skills such as patient interviewing, history taking, and symptom observation [ 17 ], which lays a foundation for their future careers.…”
Section: Introductionmentioning
confidence: 99%